Utilization of Agricultural Residues: De-Oiled Organic Rice Bran as Adsorbent of Moisturizers for Cosmetic Products - Dechprasittichok, P.; Sontag, C.; Tongtan, J.; Luachan, S. (Asian Journal of Chemistry, 2015)
The objective of this research is to study the adsorption of two types of moisturizers in cosmetic, urea and glycerin, by de-oiled organic rice bran. Urea and glycerin are moisturizers which can enhances the water-binding capacity on the skin. The samples of the de-oiled organic rice bran were obtained from Surin province of Thailand. The samples were pretreated with sodium hydroxide. In equilibrium time experiments, 0.5 g of dried de-oiled organic rice bran were immersed into 50 mL of urea or glycerin 1 % wt. solutions and shaken for various times followed by the determination of remaining moisturizer in the solution. To find the adsorption capacity of moisturizers by de-oiled organic rice bran, 0.5 g of dried de-oiled organic rice bran were immersed into 50 mL of urea or glycerin solutions with different concentration levels (1, 2, 3, 4, 5, 10, 15 and 30 g 100 mL-1). The solutions were shaken for 1,440 min. The equilibrium time for urea and glycerin was achieved at 40 and 60 min., respectively. The de-oiled organic rice bran could adsorb higher amounts of urea than glycerin. The adsorption isotherm could be well described by the Freundlich isotherm model. The findings of this study would be beneficial to evaluate the suitability and efficiency of adsorption of moisturizers by de-oiled organic rice bran for future application such as body scrub.